Reciprocity System among Muslims in Southern Philippines: The Case of Mèranao kathatabanga in Times of Natural Disasters - A. MEND0ZA, MYRMA JEAN; ABANTAS-MANALOCON, NORJANNAH; S. MAGOMNANG, ANISALAM; F. QUIRANTE, CATHERINE; AMANODEN, AMANE (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper articulates the concept of kathatabanga (reciprocity system) of the Mèranao in the context of natural disasters in Bubong, Lanao del Sur and in Pantao Ragat, Lanao del Norte. These Mèranao popula ted communities are vulnerable to natural disasters because of their geographical location. The purpose of this study is to describe the nature of kathatabanga as a Meranao mutual aid system, its notions and salient dimensions and analyze how social capital inluences the observance of kathatabanga. Guided by the social capital theory and social exchange theory, this study utilized data collected trom in depth interviews of 15 Meranao, 8 males and 7 females, aged 25-70 years whose ages range trom 25 to 70 years old.Findings of the study show that that in terms of social capital, age, gender, marital status and estimated monthly family income intluence kathatabanga. It also depicts that the Meranao kathatabanga as a practice carries with it a moral dimension which is part of Mèranao maratabat. It is also a way to strengthen kinship ties and offers an assurance and insurance. Morrover, kathatabanga, as an age old customary practice is perpetuated and intertwined with the social institutions in the Mèranao society.